Spectrophotometric analysis of caffeine and sugar content in energy drinks commonly consumed in Dhaka City, Bangladesh: A public health concern (Journal of Bangladesh Academy of Sciences, 2025)
Energy drink consumption has escalated, especially among the younger generation, credited to their stimulating properties, mainly because of their caffeine and carbohydrate contents. Given the potential health risks associated with excessive consumption of these substances, it is imperative to examine the composition of energy drink products on the market. This study used an analytical quantitative method to determine the mass concentrations of total solids, caffeine, and carbohydrates in eight brands of energy drink on sale in Dhaka, Bangladesh, using a composite, cost-effective experimental design. Total solid mass contents were 10.30 to 13.13 g per 100 mL of drinks, caffeine was found 233.30 to 546.48 mgL-1, and carbohydrates were found 7.09 to 11.15 g per 100 mL energy drink using the double beam UV-visible spectrophotometer. The accuracy of the results was also indicated by the low standard deviation values of 1.04 to 4.39 for caffeine and 0.08 to 0.23 for carbohydrate, and the relative standard deviation of 0.26 to 1.75% for caffeine and 0.54 to 2.72% for carbohydrate. There was a need for proper health, legal, and standard considerations in energy drink manufacturing, given the results.J. Bangladesh Acad. Sci. 49(2); 205-214: December 2025